Mental health and life satisfaction in a sample of students from Northern Chile - Flores, Jerome; Caqueo-Urízar, Alejandra; Vega Latorre, Guillermo; Zepeda, Aura; Rivera Bartolo, Yanira; González Ramírez, Nechelle (Revista de Psicopatología y Psicología Clínica, 2021)
It is important to specifically understand which are the mental health variables that affect the life satisfaction of children and adolescents most, in order to optimally design programs aimed at promoting their wellbeing. The relationship between mental health and life satisfaction in students aged 9 to 18 years from Northern Chile was analyzed. A correlational cross-sectional study was carried out, using the Assessment System for Children and Adolescents (SENA) and the Satisfaction with Life Scale (SWLS-C). A total sample of 3455 students was used, divided into primary and secondary school students. Two structural equation models with good fit were obtained. In both, depression, self-esteem and age were maintained. Among primary school students there also emerged problems with school. However, among secondary school students, problems related to family and gender appeared. The relationship was stronger concerning secondary school. Implications for public policies and interventions are discussed.